FY 2021-FY 2023 Medium-Term Budget. (Policy Papers; Policy Paper, 2020)
On April 27, 2020, the Executive Board of the International Monetary Fund (IMF) approved the IMF's administrative and capital budgets for financial year (FY) 2021, beginning May 1, 2020, and took note of indicative budgets for FY 2022-23.